The Effects of Spacing Practice on Learning and judgment of Learning Accuracy of Forehand Drive in Table tennis - Roza Rahavi Ezabadi; Parvaneh Shamsipour Dehkordi; Marzieh Khajezadeh (University of Tehran, 2020)
The purpose of this study was to determine the effect of distribution of practice on the acquisition, retention with different intervals 1, 7, and also judgment of learning accuracy of forehand drive in table tennis. The 32 female student with 18- 24 years old that passed specialized table tennis unit, contributed as convicted. They randomly were divided to massed and distributed practice groups. The skill used in this study was the forehand drive. After pretest, the massed group practiced all 240 Trails in one session, and the distributed practice group practiced 60 trials per day on 4 consecutive days. After acquisition phase, Participants were asked to predict performance on the retention phase. Participants were asked, "what would you predict your average score on the first the retention test? "And then half of participants of each group contributed for a retention test 1 day later, half of other participants of each group contributed for retention test 7 days later. The data were analyzed by independent sample t test and two -way analysis of variants (ANOVA) with repeated test. The result showed significant differences between massed and distributed practice groups in the acquisition, retention (1, 7) test and also judgment of learning (p